An Improved Differential Evolution Algorithm for Maritime Collision Avoidance Route Planning. (12th November 2014) - Zhao, Yu-xin; Li, Wang; Feng, Shaojun; Ochieng, Washington Y.; Schuster, Wolfgang
Abstract : High accuracy navigation and surveillance systems are pivotal to ensure efficient ship route planning and marine safety. Based on existing ship navigation and maritime collision prevention rules, an improved approach for collision avoidance route planning using a differential evolution algorithm was developed. Simulation results show that the algorithm is capable of significantly enhancing the optimized route over current methods. It has the potential to be used as a tool to generate optimal vessel routing in the presence of conflicts.